2013
DOI: 10.1542/peds.2012-3345
|View full text |Cite
|
Sign up to set email alerts
|

Pacifier Cleaning Practices and Risk of Allergy Development

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Infants with a diverse gut microbial flora are less likely to develop eczema and allergy.WHAT THIS STUDY ADDS: Parental sucking of their infant' s pacifier is associated with a reduced risk of allergy development and an altered oral flora in their child. Transfer of oral microbes from parent to infant via the pacifier might be used in primary prevention. abstract OBJECTIVE: Immune stimulation through exposure to commensal microbes may protect against allergy development. Oral micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
79
2
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(89 citation statements)
references
References 28 publications
3
79
2
5
Order By: Relevance
“…The findings of this study are consistent with those of the pacifier study by Hesselmar et al, 13 who found that children whose mothers sucked their pacifiers clean were less likely to develop allergies. Although the mechanism and age of exposure are different, both studies suggest that the immune response and risk of allergies may be influenced by exposure to oral bacteria or other microbes.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The findings of this study are consistent with those of the pacifier study by Hesselmar et al, 13 who found that children whose mothers sucked their pacifiers clean were less likely to develop allergies. Although the mechanism and age of exposure are different, both studies suggest that the immune response and risk of allergies may be influenced by exposure to oral bacteria or other microbes.…”
Section: Discussionsupporting
confidence: 92%
“…The cohort represents the full range of socioeconomic status in the South Island of New Zealand, and the study participants are mostly of New Zealand European ethnicity. Follow-up assessments were completed at ages 3,5,7,9,11,13,15,18,21,26,32, and 38 years. A full description of the study is reported elsewhere.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The children were clinically examined by pediatricians at 1.5 and 3 y of age to diagnose food allergy, eczema, asthma, and allergic rhinoconjunctivitis according to predefined protocols (38). Sensitization against common food (6-mix food) and inhalant allergens (Phadiatop) were assessed by blood tests (Phadia, Uppsala, Sweden).…”
Section: Clinical Examinationmentioning
confidence: 99%
“…These include parental mouth cleaning of pacifiers [4], hand washing dishes [5], using feather bedding materials [6], having a pet in the house [7], drinking unpasteurised milk [8] and regular visits to animal stables [9]. At first glance, putting an infant on an animal fur ( presumably largely sheepskins) to sleep might be expected to have similar effects to coming into close contact with farm animals.…”
mentioning
confidence: 99%